Anti‐tumor effects of a nonsteroidal anti‐inflammatory drug zaltoprofen on chondrosarcoma via activating peroxisome proliferator‐activated receptor gamma and suppressing matrix metalloproteinase‐2 expression. (23rd March 2018) - Higuchi, Takashi; Takeuchi, Akihiko; Munesue, Seiichi; Yamamoto, Norio; Hayashi, Katsuhiro; Kimura, Hiroaki; Miwa, Shinji; Inatani, Hiroyuki; Shimozaki, Shingo; Kato, Takashi; Aoki, Yu; Abe, Kensaku; et al.
Abstract: Surgical resection is the only treatment for chondrosarcomas, because of their resistance to chemotherapy and radiotherapy; therefore, additional strategies are crucial to treat chondrosarcomas. Peroxisome proliferator‐activated receptor gamma (PPAR γ ) is a ligand‐activated transcription factor, which has been reported as a possible therapeutic target in certain malignancies including chondrosarcomas. In this study, we demonstrated that a nonsteroidal anti‐inflammatory drug, zaltoprofen, could induce PPAR γ activation and elicit anti‐tumor effects in chondrosarcoma cells. Zaltoprofen was found to induce expressions of PPAR γ mRNA and protein in human chondrosarcoma SW1353 and OUMS27 cells, and induce PPAR γ ‐responsible promoter reporter activities. Inhibitory effects of zaltoprofen were observed on cell viability, proliferation, migration, and invasion, and the activity of matrix metalloproteinase‐2 (MMP2); these effects were dependent on PPAR γ activation and evidenced by silencing PPAR γ . Moreover, we showed a case of a patient with cervical chondrosarcoma (grade 2), who was treated with zaltoprofen and has been free from disease progression for more than 2 years. Histopathological findings revealed enhanced expression of PPAR γ and reduced expression of MMP2 after administration of zaltoprofen. These findings demonstrate that zaltoprofen could be a promising drug against the malignant phenotypes in chondrosarcomas via activation of PPAR γ and inhibition of MMP2 activity. Abstract : We first demonstrated that a nonsteroidal anti‐inflammatory drug, zaltoprofen, could activate and induce PPARγ, and elicit anti‐tumor effects on cell viability, proliferation, migration and invasion, and the activity of MMP2, which plays a critical role in tumor invasion and metastasis, in chondrosarcoma cells. As evidenced by the silencing of PPARγ, these effects were dependent on PPARγ activation.